Students’ Perspectives on Lecturers’ Code-Switching in Efl Classes and Its Impact on Students’ Speaking Skills - Hanifa Hanifa; Muyassaroh Muyassaroh (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to investigate students’ perceptions of lecturers’ code-switching practices in EFL classrooms and their impact on students’ speaking skills. Specifically, the study focuses on how code-switching supports speaking development, influences students’ confidence, and affects their attention span during the learning process.This research employed a qualitative approach using semi-structured interviews as the main data collection technique. The participants were fifth-semester students of the English Education Department at Al-Qolam University. The interview data were collected in both Indonesian and English to allow participants to express their views naturally. The data were analyzed thematically to identify recurring patterns and key themes related to code-switching and speaking skills. The findings reveal that most students perceive code-switching as a beneficial pedagogical strategy. Code-switching helps students understand learning materials more clearly, increases confidence to speak English, and creates a more supportive classroom atmosphere. Although code-switching does not directly improve speaking fluency, it indirectly supports speaking development by enhancing comprehension and reducing anxiety. However, the findings also indicate that excessive use of code-switching may lead to students’ dependency on translation, potentially limiting their exposure to English. Additionally, code-switching was found to help maintain students’ attention span, particularly when dealing with complex materials or task instructions. Based on these findings, this study recommends that lecturers use code-switching strategically and proportionally in EFL classrooms. Code-switching should function as pedagogical support rather than a substitute for English instruction, especially in speaking-focused courses. Future research is suggested to explore lecturers’ perspectives and classroom observations to gain a more comprehensive understanding of code-switching practices in EFL contexts..